Suspected Rhinolithiasis Associated With Endodontic Disease in a Cat. (December 2017) - Ng, Kevin; Fiani, Nadine; Peralta, Santiago
Rhinoliths are rare, intranasal, mineralized masses formed via the precipitation of mineral salts around an intranasal nidus. Clinical signs are typically consistent with inflammatory rhinitis and nasal obstruction, but asymptomatic cases are possible. Rhinoliths may be classified as exogenous or endogenous depending on the origin of the nidus, with endogenous rhinoliths reportedly being less common. This case report describes a suspected case of endogenous rhinolithiasis in a cat which was detected as an incidental finding during radiographic assessment of a maxillary canine tooth with endodontic disease. Treatment consisted of removal of the suspected rhinolith via a transalveolar approach after surgical extraction of the maxillary canine tooth.